(untitled) (Agricultural Engineering, 2017)
The objective of the research was to evaluate soil compaction with selected indexes and to determine the relation between them including results obtained with Proctor’s method. Measurements of penetration resistance and shear vane, dry density of soil particles (ρd) and their moisture were made in layers in the following depths: 25-30, 35-40, 45-50 and 55-60 cm. Moreover, the maximum volumetric density of soil particles, particles size distribution, content of calcium carbonate and humus, density of solid particles, reaction, plastic and liquid limit were determined with Proctor's method (ρds). Also, packing density and natural density were measured. It was found out that the investigated soils may be generally included to excessively compacted and susceptible to compaction to an average and small degree. It was shown that soil may be recognized as excessively compacted when the quotient ρd/ρds exceeds the value of 0.87.